AUTOIMMUNE ORIGIN OF SARCOIDOSIS: DETERMINATION OF SPECIFIC IMMUNE COMPLEXES IN PATIENTS WITH RESPIRATORY SARCOIDOSIS - Yu. S. Zinchenko; A. A. Starshinova; M. V. Filatov; N. V. Denisova; S. B. Landa; V. S. Burdakov; P. K. Yablonskiy (Медицинская иммунология)
The etiology of sarcoidosis is not completely understood. A hypothesis exists about the relationship between sarcoidosis and a complex of pathological autoimmune reactions that occur under the influence of triggering factors. In this study, specific immune complexes in the blood plasma of patients have been determined, which can indirectly reveal the causes of the disease.The study included 33 patients with lung sarcoidosis (I group), compared to 24 healthy donors who served as a control group (II group). The patients underwent standard examination. Their blood plasma was investigated by the dynamic light scattering method with addition of tuberculosis antigens (ESAT-6/SFP-10) and “lung healthy tissue extract”. Statistical analysis was performed using the Statistica 7.0 program. Test results were considered significant at p < 0.05.Аccording to the data obtained, addition of ESAT-6/SFP-10 to patient’s blood plasma almost did not lead to the formation of immune complexes in most samples. Meanwhile, development of such complexes after addition of “lung tissue extract” was revealed in all the patients. The immune complexes were not detected in any donor from control group after stimulation with both kinds of antigens (p < 0.01).The data on distinct formation of immune complexes with the addition of “lung healthy tissue extract” in patients with lung sarcoidosis may be considered an indirect evidence for occurrence of autoimmune reaction under the influence of some pathogenic factors. Absence of de novo immune complex formation after addition of tuberculosis antigens (ESAT-6/SFP-10) makes it unlikely any direct effects of tuberculosis bacteria upon development of sarcoidosis.